ET-CORM Mediated Vasorelaxation of Small Mesenteric Arteries: Involvement of Kv7 Potassium Channels - Zhang, Danfeng; Krause, Bernhard M.; Schmalz, Hans-Günther; Wohlfart, Paulus; Yard, Benito A.; Schubert, Rudolf (Frontiers in Pharmacology, 2021)
Although the vasoactive properties of carbon monoxide (CO) have been extensively studied, the mechanism by which CO meditates vasodilation is not completely understood. Through-out published studies on CO mediated vasodilation there is inconsistency on the type of K+-channels that are activated by CO releasing molecules (CORMs). Since the vasorelaxation properties of enzyme triggered CORMs (ET-CORMs) have not been studied thus far, we first assessed if ET-CORMs can mediate vasodilation of small mesenteric arteries and subsequently addressed the role of soluble guanylate cyclase (sGC) and that of K-channels herein. To this end, 3 different types of ET-CORMs that either contain acetate (rac-1 and rac-4) or pivalate (rac-8) as ester functionality, were tested ex vivo on methoxamine pre-contracted small rat mesenteric arteries in a myograph setting. Pre-contracted mesenteric arteries strongly dilated upon treatment with both types of acetate containing ET-CORMs (rac-1 and rac-4), while treatment with the pivalate containing ET-CORM (rac-8) resulted in no vasodilation. Pre-treatment of mesenteric arteries with the sGC inhibitor ODQ abolished rac-4 mediated vasodilation, similar as for the known sGC activator SNP. Likewise, rac-4 mediated vasodilation did not occur in KCL pretreated mesenteric arteries. Although mesenteric arteries abundantly expressed a variety of K+-channels only Kv7 channels were found to be of functional relevance for rac-4 mediated vasodilation. In conclusion the current results identified Kv7 channels as the main channel by which rac-4 mediates vasodilation. In keeping with the central role of Kv7 in the control of vascular tone and peripheral resistance these promising ex- vivo data warrant further in vivo studies, particularly in models of primary hypertension or cardiac diseases, to assess the potential use of ET-CORMs in these diseases.